PENGARUH MOTIVASI DAN ETOS KERJA TERHADAP KINERJA PEGAWAI PADA BADAN NARKOTIKA NASIONAL KOTA PEMATANGSIANTAR - Damanik, Dini; Lie, Darwin; Butarbutar, Marisi; Halim, Fitria (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2018)
As for this research problem formula is how to influence Motivation and work ethic to employee performance at Badan Narkotika Nasional Kota Pematangsiantar. Design of this research was done by using the design of library research and field research. The population used in this research is all employees at Badan Narkotika Nasional Kota Pematangsiantar which amounted to 27 employees. Considering responder amount less than 100 people to reply the questionnaires which writer propagate and availibility of writer time and also for the accuracy of result of research. Types of data used are qualitative and quantitative data. Technique of data collected by questionnaires, interview and documentation. The analysis technique used is descriptive qualitative analysis and descriptive quantitative analysis. The result of analysis from linear regression modestly that is Å¶= 6,518 + 0,827X1 + 0,314X2, it means there is a positive influence between motivation and work ethic to employee performance at Badan Narkotika Nasional Kota Pematangsiantar. The strength of relationship between the is high correlation, that is r = 0,791. From coefficient determination can be explained that the level of employee performance can be explained by motivation and work ethic as big as 62,5%, and the rest 37,5% can be explained by the other factor that was not discussed in this research. From result of processing and calculation questionnaires, writer get the conclusion that motivation and work ethic applied by Badan Narkotika Nasional Kota Pematangsiantar have an effect to employee performance. This matter is proved by hypothesis test either simultaneously where the result test fhitung (20,020) > ttabel (3,40) and which significant 0,000 < alpha 0,05. Keywords: Motivation, Work Ethic, Employee Performance